Mechanical behaviour and failure modes in the Whakaari (White Island volcano) hydrothermal system, New Zealand - Heap, M.J.; Kennedy, B.M.; Pernin, N.; Jacquemard, L.; Baud, P.; Farquharson, J.I.; Scheu, B.; Lavallée, Y.; Gilg, H.A.; Letham-Brake, M.; Mayer, K.; Jolly, A.D.; et al. (Journal of Volcanology and Geothermal Research, 2015)
International audience